Pengembangan Modul Ilmu Pendidikan Islam di STAI Ali Bin Abi Thalib Surabaya - Maryono Maryono; Zaki Ulien Nuha (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2026)
This study was motivated by the limited availability of teaching materials used in the Islamic Education Science course at STAI Ali bin Abi Thalib Surabaya. During the learning process, students relied on various separate references, resulting in learning materials that were not systematically organized or integrated into a comprehensive instructional resource. This condition made it difficult for students to understand the fundamental concepts of Islamic Education Science comprehensively and reduced the effectiveness of independent learning. The purpose of this study was to develop an Islamic Education Science module that meets instructional needs, determine its feasibility through expert validation, and describe its implementation in the learning process. The study employed a Research and Development (R&D) method consisting of needs analysis, product design, module development, expert validation, product revision, limited field testing, and final product improvement. Data were collected through observations, interviews, questionnaires, documentation, and validation by subject-matter and instructional experts. The findings revealed a strong need for an Islamic Education Science module because it helps students understand learning materials more systematically, independently, and effectively. The developed module includes learning outcomes, instructional materials, summaries, exercises, evaluations, and references organized according to the principles of Islamic education and students’ learning needs. Expert validation indicated that the module fulfilled the criteria of content validity, language appropriateness, presentation quality, and graphical design, making it suitable for instructional use. The implementation results also showed positive responses from both students and lecturers, as the module improved learning organization, facilitated understanding of course materials, and strengthened the integration of Islamic educational values into the learning process. Therefore, the developed Islamic Education Science module is considered feasible, practical, and relevant as a teaching resource for Islamic higher education institutions.